Invasive non-native fish species in the Yangtze River: A looming ecological crisis and mitigation strategies - Dawei Liu; C. Y. Jim; Chunping Xie; Senlin Hou; Xiaoming Xue (Nature Conservation)
The Yangtze River is China’s essential ecological resource and a historically revered “mother river” intimately tied to her ancient civilization. In recent years, the river has faced escalating threats from non-native fish species introduced by anthropogenic activities, including prayer animal release, aquaculture escapes, and deliberate pet abandonment. With a low current population density, these exotic species pose limited immediate ecological risks. However, the ecological damage will be catastrophic in the long run once they successfully establish large and stable populations and become invasive. To effectively address this challenge, comprehensive measures can be applied, including strengthening risk assessment, controlling reproduction and transmission, suppressing new introductions, improving regulations and policies, enhancing public education and prevention awareness, and strengthening multi-party cooperation. This study contributes new insights into the dynamics of invasive species in the Yangtze River and the broader implications for freshwater ecosystem management by reviewing current knowledge.